Taraxacum sect. Erythrocarpa in Europe in the Alps and eastwards: A revision of a precursor group of relicts - Štěpánek, Jan; Kirschner, Jan (Phytotaxa, 2022)
A taxonomic revision of Taraxacum sect. Erythrocarpa in the eastern part of Europe and in the Alps is presented. Seventeen species are recognized, nine of them are described as new. Most species occupy relatively restricted geographical ranges, the most characteristic habitats being limestone cliffs and mountain summit areas. The highest species diversity of this section is situated in the mountain ranges of Greece and the adjacent regions of Bulgaria and North Macedonia; only two species are known from the Alps, and a new species is described also from Crimea, Ukraine. Taraxacum pindicola is the only sexual diploid among the taxa studied, the other taxa exhibit agamospermy. The name T. pindicola is newly lectotypified. The northernmost representative of T. sect. Erythrocarpa, T. pieninicum (S. Poland), is conspecific with T. erythrocarpum of the western Slovakia. The names T. albomarginatum A.J. Richards and T. voricola A.J. Richards are later synonyms of T. olympophilum Sonck. Taraxacum sect. Erythrocarpa is characterized and, for each species, nomenclature, typification, a detailed description or a reference to it, diagnostic notes, distribution and habitat, and a list of herbarium specimens studied are given. Most species are illustrated, and for selected ones, distribution maps are provided.